Intervenção fonoaudiológica junto a mães de crianças com múltiplas deficiencias - Nagy, Danielle Giacometti (2005)
This essay has, as its core objective, the analysis of clinical situations that reveal a mother s difficulties in the reception, acknowledgement and care of her offspring, when the child displays multiple deficiencies. As an integral part of this, the analysis also discusses how the Speech Therapy may, in the course of therapeutic intervention, contribute for a mother s development of a greater disposition for facing the hindrances that may be presented by her child. To that end, the main theoretical basis that served as reference were Winnicott s psychoanalytic theories on the relationship between a mother and her impaired child (Winnicott, D.W. (1957). Mother and Child. A Primer of First Relationships., New York: Basic Books, Inc.), which is important in understanding the phono-audiologic work dedicated to the relationship between mother and disabled child. The methodology employed was a qualitative-clinic one with four distinct relationship dynamics being applied under frequent observation of Speech Therapy Clinic. These, once understood by the healthcare professional, may aid in the success of a particular treatment by propitiating a singular analysis of factors contributing to the dysfunctional relationship between mother and child, such as: body stigmas that prevent attachment, excessive or insufficient care, denial and hindrances to the feeding process. Seven distinct cases had their summarised profiles presented and, through categories, it was ultimately possible to understand and analyse their clinic indications. For every one among the cases, phono-audiological procedures were reviewed to demonstrate that clinical intervention may cause the psychological profile of these challenged women to be altered positively, in a manner such as to enable them to internally transform that which has brought them suffering, and assimilate it. Hence, the essay deals with a Speech Therapy intervention such, that is not restricted to the technical questions of the sort of the suitability of phono-articulatory organs, feeding or the development of communication, but open to fundamental aspects of a child s psychological development. Additionally, in so doing, this proposition will be possibly contributing to the Speech Therapyst s referential in considering developing an effort with the mothers of impaired children that surpasses the orientation and teaching of procedures to offer a basis in interventions that promote the embracing of these mothers and consequential better development of children with multiple deficiencies